Pengaruh Pariwisata, Demografi, dan Human Capital Terhadap Kemiskinan di Kawasan Timur Indonesia - Kukuh Ageng Pribowo; Diah Setyorini Gunawan; Suprapto Suprapto (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2021)
Provinces in Eastern Indonesia (KTI) have a poverty rate that is relatively higher than the Western Region of Indonesia (KBI). Tourism is a sector of global economic activity that is used by various countries in the world to increase participation in their economic growth. This study aims to determine the projected influence of tourism with the number of domestic and foreign tourists, non-productive age, and human capital measured through education and health on poverty in Eastern Indonesia (KTI) in 2010-2019. The type of this research is descriptive quantitative using panel data analysis. The results of this study indicate that the variable of domestic tourists has a negative effect on poverty, while the variable of non-productive age has a positive effect on poverty. The variables of the number of foreign tourists, education, and health have no effect on poverty in Eastern Indonesia (KTI). These results imply that 1) the government must involve local communities in tourism development, 2) the government must issue policies to regulate non-productive population growth, 3) education improvement must also hone life skills, 4) health facilities and services must able to touch all levels of society